2006
DOI: 10.2214/ajr.05.1192
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Stromal Tumors Treated with Imatinib: Monitoring Response with Contrast-Enhanced Sonography

Abstract: Contrast-enhanced Doppler sonography is a noninvasive imaging technique that allows the early prediction of tumor response in c-kit-positive GIST treated with Glivec.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 185 publications
(106 citation statements)
references
References 30 publications
1
102
0
3
Order By: Relevance
“…Alternatively, if mutation status is not determined before treatment, we may also check response very early by computed tomography, positron emission tomography, or contrast-enhanced ultrasound. 10 If a radiographic response is detected within a month, then the mutation status is likely favorable, and the treatment may be continued without necessarily pursuing mutation testing. If not, then mutation status should be investigated before continuing the treatment.…”
Section: Primary Diseasementioning
confidence: 99%
“…Alternatively, if mutation status is not determined before treatment, we may also check response very early by computed tomography, positron emission tomography, or contrast-enhanced ultrasound. 10 If a radiographic response is detected within a month, then the mutation status is likely favorable, and the treatment may be continued without necessarily pursuing mutation testing. If not, then mutation status should be investigated before continuing the treatment.…”
Section: Primary Diseasementioning
confidence: 99%
“…Our data bring up the first evidence of (a) a host-derived factor in dictating GIST outcome during IM therapy (3,44,45), of (b) a prognostic effect of NK cell functions in solid tumors, and of (c) an immunologic ''off-target'' effect on NK cells of a tyrosine kinase inhibitor. A larger patient series will be needed to validate the prognostic value of an augmented NK cell IFN-g production at 2 months of IM therapy and to establish the added value of this immunologic parameter over that of the c-kit mutation status or ultrasonography (46). …”
Section: Discussionmentioning
confidence: 99%
“…These studies have indicated that DCE-US parameters may be correlated with tumor responses, for example in RCC with sorafenib (7,8) or in gastrointestinal stromal tumors (GIST) treated by imatinib (9).…”
Section: )mentioning
confidence: 99%